PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IIIB SDN 001 KAMPAR TIMUR - Iin Rahayu Putri; Syahrilfuddin Syahrilfuddin; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to improve student learning outcomes SDN class IIIb Kampar 001 Kampar Timur through the implementation of cooperative learning model Numbered Head Together. This study was conducted in SDN 001 East Kampar in class IIIB, while the time the study was conducted in the academic year 2015/2016. As the subjects in this study were teachers and students of class IIIB SDN 001 Kampar Timur, with a total of 25 students, consisting of 11 men and 14 women. Design of this research is the Classroom Action Research (PTK). From the results, it can be concluded the implementation of cooperative learning model Numbered Head Together can improve learning outcomes IIIb IPS graders of SDN 001 Kampar Timur. The increase of the average score of the base to the first cycle at an average of 58.52 into 71.20 with an increase of 12.68 (76%). An increase from the first cycle to the second cycle, ie from an average of 71.20 into 77.60 with an increase of 6.4 (96%). Based on the conclusions and the discussion on the above results, related to the application of the model Numbered Head Together has been done, the teacher asked a few suggestions, namely: It is expected that teachers plan to improve the situation of the discussion thus further enhance students' activity in learning activities in the classroom with the type cooperative learning Numbered Head Together in the learning process IPS.Key Words: learning outcomes IPS, Numbered head together